The Relevance Of Spiritual Intelligence In The Independent Curriculum: Responding To The Challenges Of Digital Disruption In Islamic Educational Institutions - Fitri Wahyuningsih; Zoni Leo Nardo; Nana Sepriyanti; Martin Kustati (International Journal of Technology and Education Research, 2026)
Digital disruption has give birth to various challenge Serious for institution Islamic education, such as flood information unfiltered, exposure content negative that is not unstoppable, and moral crisis marked with cyber disorientation, the spread of hoaxes, and moral disengagement among participant education. Research This aim For analyze relevance spiritual intelligence in Independent Curriculum as solution answer challenge mentioned in the institution Islamic education. Type of research This is studies library with analyze various source relevant literature. Research results show that First, spiritual intelligence in Islamic perspective is based on the concept of fitrah and is very urgent in the era of digital disruption as moral compass and internal fortress of spiritual degradation. Second, the Independent Curriculum through Profile Pancasila Students and Profile Students Grace Lil Alamin provides room open for integration values spiritual intelligence in general holistic through approach transinternalization and projects strengthening profile. Third, spiritual intelligence plays a role significant in fortify participant educate from cyber disorientation, hoaxes, and moral disengagement through awareness transcendental will supervision divine. Fourth, there is four implementation models effective that is integration curricular, habituation and acculturation, projects strengthening profile, as well as necessary role models combined in a way synergistic. Research This conclude that spiritual intelligence has strong relevance​ with Independent Curriculum and become inevitability in institutions Islamic education. Implementation results study covers compilation policy integrated, improved teacher capacity in spiritual pedagogy, creation healthy digital ecosystem, exemplary behavior consistent from educators, as well as monitoring and evaluation sustainable.